1594. Evaluating Clinical Outcomes of an Alternative Cefepime Dosing Regimen as Empiric Antibiotic Therapy in Hospitalized Adults with Febrile Neutropenia. (26th November 2018) - Haiduc, Manuela; Bremmer, Derek; Patel, Monank; Walsh, Thomas; Moffa, Matthew
Abstract: Background: A cefepime dosing regimen of 1 g every 6 hours (1 g Q6h) has shown to provide similar exposure above the target minimum inhibitory concentration than the higher FDA-approved regimen of 2 g Q8h for febrile neutropenia. We hypothesize clinical outcomes among patients receiving either dosing strategy will be similar. Methods: A retrospective chart review of hospitalized patients who received cefepime for documented febrile neutropenia over a two-year period was performed. Patients were grouped based on cefepime dosing strategy: 1 g Q6h vs. 2 g Q8h. The primary objective was to compare time to defervescence after cefepime initiation. Secondary objectives looked at all-cause and infection-related 30-day mortality, duration of therapy, and length of stay (LOS). Results: Seventy-five patients in each arm were included. There were no differences in baseline age or severity of illness between groups. There was no difference in the primary objective as average time to defervescence was similar between the 1 g Q6h and 2 g Q8h groups (85.9 hours vs. 89.7 hours: P = 0.206), respectively. Additionally, no differences were found in the secondary objectives including all-cause 30-day mortality (6.7% vs. 9.3%: P = 0.547), duration of therapy (95.7 hours vs. 99.1 h: P = 0.174), or LOS (9 vs. 7 days: P = 0.251). Conclusion: The regimen of cefepime 1 g Q6h provides similar clinical outcomes as the traditional FDA-approved 2 g Q8h regimen in the treatment of febrile neutropenia. The lower total daily dose will result in less drug exposure and a potential decreased risk of cefepime-related adverse drug events. Disclosures: All authors: No reported disclosures.